Psychological analysis of novel “Amba” by Lakme Pamuntjak - Adernarsy Avereus Rahman (Universitas Indraprasta PGRI, 2017)
Literary work is the result of creative writing containing aesthetic values and the values of life conveyed through the meanings of the story. Narrating a story of literary works involves the roles’ of the characters as the main figures that is consistent with the story and a psychological analysis of literary. The method used in this research was descriptive qualitative method. The data sources used were documents such as the review of the Novel amba. Data collection was done by using documentation and interviews. The results of this research are as follows: (1) dispositive key figures were illustrated by using the method of standpoint. (2) id aspect of the characters in the novel of Amba comes from life and death instincts as the form of survival or fulfilling the needs. (3) aspects of ego that exists in figures Novel amba are served as a means of meeting the needs and as a determinant in deciding any actions to take in response to the problems that occur within the characters. (4) aspects of the superego is depicted through the picture of them obeying the rules that exist in the society.